2019
DOI: 10.1200/po.18.00217
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Prospective Cohort Study of the Diagnostic Yield and Patient Experience of Multiplex Gene Panel Testing For Hereditary Cancer Risk

Abstract: Purpose Multiplex gene panel testing (MGPT) allows for the simultaneous analysis of germline cancer susceptibility genes. This study describes the diagnostic yield and patient experiences of MGPT in diverse populations. Patients and Methods This multicenter, prospective cohort study enrolled participants from three cancer genetics clinics—University of Southern California Norris Comprehensive Cancer Center, Los Angeles County and University of Southern California Medical Center, and Stanford Cancer Institute—w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 45 publications
2
45
0
3
Order By: Relevance
“…Multigene panel testing allows for an efficient approach to determine a potential genetic cause for inherited cancer susceptibility [1]. However, the clinical utility of such testing remains in question as many genes included on panels are moderate-risk genes with less established data on cancer risk estimates and risk management [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multigene panel testing allows for an efficient approach to determine a potential genetic cause for inherited cancer susceptibility [1]. However, the clinical utility of such testing remains in question as many genes included on panels are moderate-risk genes with less established data on cancer risk estimates and risk management [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative studies investigating patient outcomes after undergoing multigene panel testing for cancer susceptibility demonstrated increased levels of anxiety and uncertainty in those who test positive for a pathogenic variant [1,8,9]. Other studies have found that uncertainty and anxiety are not predominant feelings among individuals who pursue genetic testing for cancer susceptibility, and that in fact, learning about cancer risk provides individuals with an opportunistic sense to be more proactive about their healthcare [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…16,17,19 We conducted a multicenter, prospective study of a hereditary cancer panel in a diverse cohort of 1264 participants responding to a survey 3 months after disclosure of the results. 21 We hypothesized that panel testing would be received favorably overall but that high-risk PV carriers would have higher levels of distress than other participants, whereas moderate-risk PV carriers would have higher levels of uncertainty than other participants. The results of our study will inform cancer genetic counseling and testing strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Of 149 patients with high-penetrance PGVs, 42 (28.2%) had clinically actionable management and treatment changes including targeted therapy ( n = 21), enrollment in clinical trials ( n = 2), and surgery ( n = 18). In the study reported by Idos et al, 12% of 2000 patients harbored PGVs [ 47 ]. Sixteen of those tested positive underwent prophylactic surgery.…”
Section: Discussionmentioning
confidence: 99%